(untitled) (World Science, 2021)
The article provides data on the results of the study of seven varieties of winter wheat. According to the data obtained, the growth and development of winter wheat varieties differ depending on the characteristics of weather and climatic conditions and the genotypic properties of winter wheat varieties. Thus, in the growing season favorable in terms of heat supply, the leaf area and the accumulation of dry matter were higher than the hot growing season. Analysis of the technological properties of wheat also showed that these indicators change depending on the genotype of varieties and the prevailing conditions of the spring-summer period. Thus, during the growing season favorable in terms of heat supply, the leaf area and the accumulation of dry matter were higher than during the hot growing season. Analysis of the technological properties of wheat also showed that these indicators change depending on the genotype of the variety and the prevailing conditions of the spring-summer period.